Does the Timing of 1-Stage Palatoplasty With Radical Muscle Dissection Effect Long-Term Midface Growth? A Single-Center Retrospective Analysis. (February 2022) - Shetty, Vikram; Patteta, Nanda Kishore; Yadav, Anirudh; Bahl, Devyani; Sailer, Hermann F.
Objective: To evaluate the long-term effect of timing of 1-stage palatoplasty on midfacial growth in patients with cleft lip and palate (CLP). Design: Retrospective observational cohort study. Study Setting: Institutional hospital. Patients: One hundred twelve patients with CLP who underwent palatoplasty and were divided into 3 groups: group I: operated between 9 and 11 months; group II: operated between 18 and 20 months; and group III: operated between 21 and 24 months. Interventions: All patients underwent von Langenbeck palatoplasty technique, which was converted to a Bardach 2-flap technique in case of any technical difficulties. The patients were followed up between 8 and 9 years when they reported for secondary alveolar bone grafting. Postsurgical cephalometric and dental casts measurements were taken for midfacial growth analysis. Main Outcome Measures: The cephalometric measures were analyzed for midfacial growth and compared within the groups. Results: Statistically significant difference ( P < .01) was found on comparing the cephalometric parameters such as sella–nasion–A point angle (SNA), A point–nasion–B point angle (ANB), n toperpendicular to point A (N-perpA), condylon to point A (Co-A), anterior nasal spine to posterior nasal spine (ANS-PNS), nasion to Anterior nasal spine (N-ANS), nasion to menton (N Me), and witts appraisal (Witt (AO-BO)) in group I when compared to both group II and group III patients, implying deficient midfacial growth in group I. No statistical difference was found in the cephalometric values between group II and group III. Group II had better cephalometric measurements than group III, showing better growth in group II than group III. Overall, there was less incidence of midfacial hypoplasia in patients treated between 18 and 20 months (group II). Conclusion: We conclude that palatal closure carried out at 18 to 20 months and 21 to 24 months is associated with better midfacial growth when compared to closure at 9 to 11 months. The best time to operate would be between 18 and 20 months to avoid speech disturbances. Midfacial growth can be greatly influenced by the timing of 1-stage palatoplasty.